Experience with Livaditis circular myotomy in management of long gap TEF - Amit Singh; Minu Bajpai; Nitin Sharma; Shashanka Shekhar Panda (Wolters Kluwer Medknow Publications, 2014)
Background: Management of long gap oesophageal atresia with tracheoesophageal fistula (OA TEF) is challenging. Various intra-operative and pre-operative manures have been described to tackle this challenge. We reviewed our experiences with livaditis circular myotomy. The aim of this study was to evaluate long-term outcomes in cases of long gap OA TEF managed primarily with livaditis circular myotomy. Materials and Methods: This is a cross-sectional study including cases of long gap oesophagus managed by livaditis circular myotomy between January 1998 and October 2012. Their case records were evaluated for operative and post-operative data. The anthropometric data of these cases were collected. All these cases were subjected to barium swallow and manometry. Those cases with other associated neurological anomalies, multiple congenital anomalies, parents refusing consent for the study, less than 6 months of follow up or incomplete data were excluded from the study. Results: Out of the total of 109 patients of OA TEF managed, long gaps OA TEF were 37. Out of the 37 cases, 13 were managed by primary repair with livaditis circular myotomy. Of these 13 cases, 11 formed the study group. Mean age at evaluation was 36 ± 9 months. Mean age at primary surgery was 3 ± 2.5 days of life. Minor leak in the immediate post-operative period was present in 2/11 cases. Manometry was done in all the cases and revealed motility disorder in the form of un-coordinated contraction in 4/11 cases. Remaining 7/11 cases were normal. Conclusion: Livaditis circular myotomy is a viable option in the management of long gap OA TEF with good comparable long-term results.